The potential use of drones for tourism in crises: A facility location analysis perspective - Shiva Ilkhanizadeh; Mahmoud Golabi; Siamand Hesami; Husam Rjoub (Journal of Risk and Financial Management, 2020)
Considering the recent lockdowns and travel bans due to COVID-19, novel tourism strategies are necessary to face the increasing need for innovative products and services and to ensure long-term sustainable growth. This study looks into the potential use of drones in providing online virtual tours of open-space tourist attractions. To do so, a novel mixed-integer linear mathematical model is developed to optimally determine the number and location of required facilities and the number of drones assigned to each center. The model is applied to a case study of Rome by selecting six historic sites as the tourist attractions and considering several candidate locations for establishing the facilities. The results of different potential scenarios imply that the project is profitable, even if the demand for virtual tours is low.
Keywords: 330; COVID-19; drone; drone tourism; facility location problem; unmanned aerial vehicle; virtual tourism